Design and Implementation of a Web-Based Printing Service System Using UML and Waterfall: A Case Study of Business Process Optimization - Deni Apriadi; Arie Rafika Dewi (Journal of Information Technology and Systems Engineering, 2026)
The rapid advancement of information technology has encouraged service-based industries, including printing services, to adopt digital systems to improve operational efficiency and data accuracy. However, many small and medium-sized printing enterprises still rely on manual or semi-digital processes, leading to miscommunication, data inconsistencies, and inefficient workflow management. This study aims to design and implement a web-based printing service system using the Unified Modeling Language (UML) and the Waterfall development model to optimize business processes. A qualitative case study approach was employed, with data collected through observation, interviews, and documentation at CV. Rakha Media Group. The system integrates order management, inventory control, payment processing, and production workflow into a unified platform. System evaluation was conducted using Black-Box and White-Box testing, as well as ISO/IEC 25010 and the System Usability Scale (SUS). The results indicate that the system achieves a 100% functional success rate, a SUS score of 74.1 (good usability), and an overall quality score of 89% based on ISO 25010 evaluation. These findings demonstrate that the proposed system effectively reduces operational errors, improves communication between departments, and enhances overall efficiency. This study contributes both theoretically, by reinforcing the role of integrated information systems in business process optimization, and practically, by providing a scalable solution for digital transformation in printing service enterprises.